Evaluation of the Anticancer Potential of Alchemilla vulgaris Extract Against Human Neuroblastoma Cells - Moqidem, Yomna (AUC Knowledge Fountain, 2021)
Neuroblastoma is one of the most challenging pediatric tumors that present heterogeneity in prognosis and survival despite intensive treatment protocols. Therefore, there is an urge to develop novel and more potent anticancer drugs. Medicinal plants have recently gained worldwide attention due to their variable activities, wide availability, and cost-efficiency. Accordingly, this study attempted to identify novel plant extracts that could show potential anticancer properties against neuroblastoma. In this study, Alchemilla vulgaris (A.vulgaris) ethyl acetate extract was prepared and evaluated for its anticancer potential against SH-SY5Y Human neuroblastoma cell line. The Phenolic content of the prepared extract was characterized using HPLC and GC-MS studies. The anticancer Evaluation studies included cell viability, clonogenicity, cellular and nuclear morphology, cytotoxicity, migratory ability, and gene expression analysis. Results showed that the prepared extract was highly enriched with an enormous variety of phenolic compounds, and it significantly reduced SH-SY5Y percentage viability in a dose and time-dependent manner; the least half-maximal inhibitory concentration (IC50) value obtained was after 48h incubation (12.29 μg/ml; 95% confidence interval: 11.83 to 12.77 μg/ml) to be only four times higher than IC50 value of the potent anticancer drug, Cisplatin, used in the standard protocol of treatment. A. vulgaris extract significantly reduced rates of clonogenic cell survival and migration and increased the number of dead neuroblastoma cells. Examinations of Cellular and nuclear morphology suggests that cell death was through apoptosis induction. Gene expression analysis shows a significant down-regulation of the cell cycle genes (CDK4, CDK6, and E2F3), and up-regulation of the tumor suppressor gene PTEN. These results illustrate that the multiple anticancer properties of A. vulgaris extract, which might have been induced through molecular alterations of the tumor suppressor PTEN and cell cycle genes.